Triiodothyronine (T3) does not induce rankl expression in rat ROS 17/2.8 Cells - Saraiva, Patrícia P. [UNESP]; Teixeira, Silvania S. [UNESP]; Nogueira, Célia Regina [UNESP]; Padovani, Carlos Roberto [UNESP] (FapUNIFESP (SciELO), 2008)
Osteoclastogenesis may be regulated via activation of the RANK/RANKL (receptor activator of nuclear factor-kappa B/ receptor activator of nuclear factor-kappa B ligand) system, which Is mediated by osteoblasts. However, the bone loss mechanism induced by T3 (triiodothyronine) is still controversial. In this study, osteoblastic lineage rat cells (ROS 17/2.8) were treated with T3 (10-8M, 10-9M, and 10-10M), and RANKL mRNA (messenger RNA) expression was measured by semiquantitative RT-PCR. Our results show that T3 concentrations used did not significantly enhance RANKL expression compared to controls without hormone treatment. This data suggests that other mechanisms, unrelated to the RANK/RANKL system, might be to activate osteoclast differentiation in these cells. copyright © ABE&M todos os direitos reservados.
Keywords: Bone; RANKL; Rat; ROS17/2.8 cell; Thyroid hormone